STRATEGI CLEAN CLOTHES CAMPAIGN DALAM MENGADVOKASI HAK BURUH PEREMPUAN DI INDUSTRI FAST FASHION: STUDI KASUS JABA GARMINDO DI INDONESIA - Salsabilla, Dhiyya; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This research analyzes Clean Clothes Campaign's (CCC) transnational advocacy for women workers' severance rights at PT Jaba Garmindo. Utilizing a qualitative case study and the Transnational Advocacy Network (TAN) framework, it examines the use of information, symbolic, leverage, and accountability politics via a boomerang pattern against Uniqlo and s.Oliver. Findings reveal that these strategies secured partial financial relief from s.Oliver but faced resistance from Uniqlo. The study concludes that non-state actors' effectiveness in global governance is constrained by voluntary compliance and power asymmetries within buyer-driven supply chains. Keywords: Clean Clothes Campaign, Women Workers, Fast Fashion, Transnational Advocacy Network, Jaba Garmindo.